Categorical consequence for paraconsistent logic - Woodruff, Peter W., author; Johnson, Fred (Frederick A.), author; Filosofia, publisher (Colorado State University. Libraries, 1999)
Consequence relations over sets of "judgments" are defined by using "overdetermined" as well as "underdetermined" valuations. Some of these relations are shown to be categorical. And generalized soundness and completeness results are given for both multiple and single conclusion categorical consequence relations.
Keywords: consequence relations; truth value gaps